PENDIDIKAN AGAMA KATOLIK SEBAGAI SARANA PEMBENTUKAN SIKAP TOLERANSI BERAGAMA ANTAR PESERTA DIDIK DI ERA DIGITAL DI SD INPRES WERI - Susana Soi Leton; Yosep Belen Keban (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The digital era has a significant impact on social life, including in terms of religious tolerance. Students are now more easily exposed to information from various digital sources that do not necessarily support the values ​​of tolerance. This phenomenon is a challenge for the world of education, especially in instilling an attitude of mutual respect amidst diversity. This study aims to determine the role of Catholic Religious Education as a means of forming an attitude of religious tolerance among students in the digital era at SD Inpres Weri. This study uses a qualitative method with a descriptive approach. The subjects of the study consisted of Catholic Religious Education teachers, principals, and students. Data collection techniques through observation, interviews, and documentation. Data analysis techniques with data reduction, data presentation, drawing conclusions. The results of the study show that Catholic Religious Education plays an important role in instilling the values ​​of love, forgiveness, respect for differences, an d forming an open and peaceful Christian character. Teachers also act as role models in guiding students to face diversity positively. This study confirms that Catholic Religious Education contributes to forming a tolerant attitude of students, especially amidst the challenges of the digital era.